THE INFLUENCE OF LIGHTING, FLOOR TYPE AND WALL TYPE ON THE PULMONARY TUBERCULOSIS IN FARMERS : Pengaruh Pencahayaan, Jenis Lantai dan Jenis Dinding terhadap Kejadian TBC Paru pada Petani - Adha, Aziza Zahrotul; Kinanthi, Citra Anggun; Widati, Sri; Kwan Ching, Wong Arkers (Universitas Airlangga, 2025)
Background: Mycobacterium tuberculosis is the bacterium responsible for tuberculosis (TB), a disease primarily spread through droplets from infected individuals. Ponorogo Regency ranks eighth in TB-related mortality in East Java, with Kauman Health Center recording the highest number of TB cases, most of which involve individuals working as farmers. This study aims to investigate how environmental factors such as lighting, floor type, and wall type contribute to the occurrence of pulmonary TB among farmers in the Kauman Health Center area. Methods: This research employed an analytical observational design with a case-control approach. A total of 78 who worked as farmers were included, consisting of 39 cases and 39 controls, selected through simple random sampling. Both primary and secondary data were collected using measurement and observation techniques. The study focused on pulmonary TB incidence as the dependent variable, while the independent variables included lighting, floor type, and wall type. Data analysis involved univariate and bivariate methods using logistic regression. Results: Findings showed that the majority of respondents lived in homes with inadequate lighting (72%), proper floor types (79%), and acceptable wall types (69%). A significant association was identified between poor lighting and TB incidence among farmers, OR = 3.659 (95% CI: 1.422–9.417). However, no significant relationship was found between TB incidence and either floor type (p=0.366) or wall type (p=0.113). Conclusion: Inadequate lighting is significantly associated with pulmonary TB in farmers. In contrast, the type of floor and wall materials did not significantly influence this study.